Effects of awake prone position vs. usual care on acute hypoxemic respiratory failure in patients with COVID-19: A systematic review and meta-analysis of randomized controlled trials - Peng, Qing; Yang, Sheng; Zhang, Yu; Zhao, Wenjie; Hu, Man; Meng, Bo; Ni, Huanhuan; Min, Lingfeng; Yu, Jiangquan; Wang, Yongxiang; Zhang, Liang (Frontiers in Medicine, 2023)
Background Previous studies have shown that an awake prone position may be beneficial for the treatment of acute respiratory distress syndrome (ARDS) or acute hypoxic respiratory failure (AHRF) in patients with COVID-19, but the results are not consistent, especially in terms of oxygenation outcomes and intubation rate. This systematic review and meta-analysis assessed the effects of the awake prone position on AHRF in patients with COVID-19 with all randomized controlled trials (RCTs). Methods An extensive search of online databases, including MEDLINE, Embase, Web of Science, and Cochrane Central Register of Controlled Trials from 1 December 2019 to 30 October 2022, with no language restrictions was performed. This systematic review and meta-analysis are based on the PRISMA statement. We only included RCTs and used the Cochrane risk assessment tool for quality assessment. Results Fourteen RCTs fulfilled the selection criteria, and 3,290 patients were included. A meta-analysis found that patients in the awake prone position group had more significant improvement in the SpO2/FiO2 ratio [mean difference (MD): 29.76; 95% confidence interval (CI): 1.39–48.13; P = 0.001] compared with the usual care. The prone position also reduced the need for intubation [odd ratio (OR): 0.72; 95% CI: 0.61 to 0.84; P < 0.0001; I2 = 0%]. There was no significant difference in mortality, hospital length of stay, incidence of intensive care unit (ICU) admission, and adverse events between the two groups. Conclusion The awake prone position was a promising intervention method, which is beneficial to improve the oxygenation of patients with ARDS or AHRF caused by COVID-19 and reduce the need for intubation. However, the awake prone position showed no obvious advantage in mortality, hospital length of stay, incidence of ICU admission, and adverse events. Systematic review registration International Prospective Register of Systematic Reviews (PROSPERO), identifier: CRD42022367885.